Differential effect of motivational features on training improvements in school-based cognitive training - Katz, Benjamin; Jaeggi, Susanne; Buschkuehl, Martin; Stegman, Alyse; Shah, Priti (Frontiers in Human Neuroscience, 2014)
Cognitive training often utilizes game-like motivational features to keep participants engaged. It is unclear how these elements, such as feedback, rewards, and theming impact player performance during training. Recent research suggests that motivation and engagement are closely related to improvements following cognitive training. We hypothesized that training paradigms featuring game-like motivational elements would be more effective than a version with no motivational elements. Five distinct motivational features were chosen for examination: a real-time scoring system, theme changes, prizes, end-of-session certificates, and scaffolding to explain the lives and leveling system included in the game. One version of the game was created with all these motivational elements included, and one was created with all of them removed. Other versions removed a single element at a time. Seven versions of a game-like n-back working memory task were then created and administered to 128 students in 2nd through 8th grade at school-based summer camps in southeastern Michigan. The inclusion of real-time scoring during play, a popular motivational component in both entertainment games and cognitive training, was found to negatively impact training improvements over the three day period. Surprisingly, scaffolding to explain lives and levels also negatively impacted training gains. The other game adjustments did not significantly impact training improvement compared to the original version of the game with all features included. These findings are preliminary and are limited by both the small sample size and the brevity of the intervention. Nonetheless, these findings suggest that certain motivational elements may distract from the core cognitive training task, reducing task improvement, especially at the initial stage of learning.